Evaluation of Habitat Management as a Tool for Wildlife Conservation in Ode-Irele, Ondo State, Nigeria - Adeleke, Bola Olusola (My University, 2017)
Forest loss may infringe on the capacity of the forest ecosystem to carry out its numerous environmental services. This study was conducted in the forested belt of Ode-Irele, Ondo state, Nigeria. Two staged sampling technique was adopted with enumeration area being the first stage and households were the second stage. Two thousand copies of questionnaires were randomly administered to households in ten enumeration areas. Univariate analysis of variance was carried out on the respondents' level of agreement on the sensitivity of wildlife to environmental disturbance. Results showed that urban arboreta as homes for wildlife were the most sensitive. Majority (91%) of the respondents agreed that the use of chemicals kills important wild animals. All respondents agreed that forest reserves helped in protecting wild animal population, while 82% agreed that leaving forest next to another forest helps to increase total home for wild animals. Majority (91%) agreed that leaving forest on the bank of a river helped to increase total home for wild animals. Also, 82% and 85% of the respondents respectively approved of managing forest for carbon breakdown, and protection of water catchment areas. Majority (93%) approved of preservation of natural scenic beauty, particularly for tourism, as 84% approved that entrance fees should be paid for admission into private lands for collection of information. Rewards encourages involvement in sustainable forest management thus improving sustainable forest and environmental stewardship.
Keywords: Environmental Resources; Forest; Ode-Irele; Wildlife Conservation; Habitat